1997
DOI: 10.1128/iai.65.5.1842-1848.1997
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Escherichia coli O157:H7 in the intestines of neonatal calves

Abstract: Cattle are an important reservoir of Shiga toxin-producing enterohemorrhagic Escherichia coli (EHEC) O157:H7 strains, foodborne pathogens that cause hemorrhagic colitis and hemolytic uremic syndrome in humans. EHEC O157:H7 strains are not pathogenic in calves >3 weeks old. Our objective was to determine if EHEC O157:H7 strains are pathogenic in neonatal calves. Calves <36 h old inoculated with EHEC O157:H7 developed diarrhea and enterocolitis with attaching and effacing (A/E) lesions in both the large and smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(87 citation statements)
references
References 40 publications
4
81
0
2
Order By: Relevance
“…Dean-Nystrom and colleagues [49][50][51] demonstrated by experimental inoculation that E coli O157:H7 can cause A/E lesions, enterocolitis and diarrhea in both colostrumdeprived and colostrum-fed neonatal calves, and A/E lesions without diarrhea in 3to 4-month-old weaned calves. In addition, they demonstrated that intimin expression by the infecting organism is necessary for the formation of A/E lesions and subsequent colonization.…”
Section: Disease In Calves Caused By E Coli O157:h7 and O157:nm Infecmentioning
confidence: 99%
See 1 more Smart Citation
“…Dean-Nystrom and colleagues [49][50][51] demonstrated by experimental inoculation that E coli O157:H7 can cause A/E lesions, enterocolitis and diarrhea in both colostrumdeprived and colostrum-fed neonatal calves, and A/E lesions without diarrhea in 3to 4-month-old weaned calves. In addition, they demonstrated that intimin expression by the infecting organism is necessary for the formation of A/E lesions and subsequent colonization.…”
Section: Disease In Calves Caused By E Coli O157:h7 and O157:nm Infecmentioning
confidence: 99%
“…In addition, they demonstrated that intimin expression by the infecting organism is necessary for the formation of A/E lesions and subsequent colonization. 50 Dean-Nystrom and colleagues 49 reported, ''EHEC O157:H7 pathogenicity in cattle appears to be age related, even within the neonatal period.'' The virulence of EHEC O157:H7 bacteria was greater in calves inoculated when less than 12 hours old than in those 30 to 36 hours old.…”
Section: Disease In Calves Caused By E Coli O157:h7 and O157:nm Infecmentioning
confidence: 99%
“…Coexistence between EPEC/EHEC strains and other diarrhoeagenic agents has already been noticed in field studies and may be related to the severity and persistance of diarrhoea in farms [5]. The age of the animal is also important: with strains of serotypes O157:H7 and O26:H11 clinical signs could not be reproduced in calves aged one to two weeks but could be reproduced well in newborn calves [1,6,7,18]. The opposite situation may exist for strains belonging to other serotypes, mimicking the situation of EPEC in rabbits [21,26].…”
Section: Discussionmentioning
confidence: 91%
“…As no other classical diarrhoeagenic infectious agents were isolated from these two calves and as the control calf did not develop diarrhoea [7], the O118:H16 EHEC strain can be considered the cause of diarrhoea. It may be argued that challenge with any bacteria would cause the appearance of diarrhoea.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation